Development of a participatory model involving community leaders and families in the care of psychiatric patients in Ban Thi District, Lamphun Province - Kiatanant, Somsakun (Health Science, Science and Technology Reviews, 2025)
This study aimed to investigate and develop a model for the participation of community leaders and families in the care of community-dwelling psychiatric patients in Ban Thi District, Lamphun Province, between May and September 2024. The sample consisted of 216 individuals divided into three groups: the Ban Thi District Health Service Network, families of psychiatric patients, and psychiatric patients, with 72 participants in each group. Each group was further divided into an experimental group (n=36) that received the intervention according to the developed model for 8 weeks, and a control group (n=36) that received standard care according to the Ministry of Public Health guidelines. Data were analyzed using Paired sample t-tests and Independent t-tests. The study results showed that the experimental groups demonstrated statistically significant improvements (p<0.05) in several aspects when comparing pre- and post-intervention scores. Specifically, the Health Service Network group showed improvements in depression screening, depression level assessment, suicide risk assessment, knowledge scores, attitude scores, and behavior scores. The families of psychiatric patients showed improvements in suicide risk assessment, knowledge scores, attitude scores, and behavior scores. The psychiatric patient group showed improvements in violent behavior, depression level assessment, and suicide risk assessment. When comparing the experimental and control groups after the intervention, the experimental groups in all three categories exhibited significantly better scores (p<0.05). The Health Service Network group showed higher scores in depression level assessment, suicide risk assessment, knowledge, attitude, and behavior. The families of psychiatric patients showed higher scores in depression screening, knowledge, attitude, and behavior. The psychiatric patient group showed higher scores in depression screening and depression level assessment. The findings of this study highlight the importance of integrating collaboration among public and private sector networks to establish working mechanisms and promote community participation in the care of psychiatric patients. This collaborative approach is expected to lead to reduced stigma and sustainable improvement in the quality of life for psychiatric patients.